The big city - Gilmore, Grace (Gilmore, Grace. Tales from Maple Ridge, 2015)
Logan Pryce and his father spend a day in the big city of Sherman, but despite his eagerness to leave "boring" Maple Ridge, Logan is glad to return to quiet, familiar surroundings after the hustle and bustle of the city.